Using body mapping as part of the risk assessment process – a case study. Issue 2 (3rd July 2018) - Thomas, David; Hare, Billy; Cameron, Iain
Abstract: This paper reports on a study undertaken to identify levels of MSD in relation to methods of waste collection. The need to quantify and eliminate ill health arising out of work is vital to reduce workplace absence leading to debate on associated relationships between the methods of waste collection and musculoskeletal disorders (MSDs). Body mapping is a participatory research tool that has been successfully used to investigate workplace ill health problems. Participatory body mapping exercises were carried out using staff at a UK District Council 2 years before and after the move from boxes and baskets to a wheeled bin recycling service. The study introduces the concept of Average Pain Count (APC). The data support previous studies showing that wheeled bin-based services (APC 2.07 & 2.80) are associated with less MSD outcomes than services including boxes, baskets and sacks (APC 4.02). The surveys provided compelling evidence to suggest that there are associations between age and self-reported pain, although there appeared to be no patterns with regard to length of service. These findings should help Local Authorities better understand critical factors regarding waste collection strategies and self-reported pain. There are recommendations regarding the use of body mapping and for industry practice.